Implementasi Metode Iqro’ dalam Pengajaran Mengaji Studi Kasus Desa Kesamben - Zuhri Adi Brata, Hilmi; Widyastuti Herawati, Yayuk; Syihab, Azhar Saaidin (Jurnal Makkareso, 2024)
This research aims to discuss the implementation of the Iqro' method in the process of teaching Quran recitation, taking the case study of Kesamben Village. The Iqro' method is known as an approach to learning Quranic reading that emphasizes gradual learning of Quranic letters and words. This study evaluates the effectiveness of implementing the Iqro' method in improving Quranic reading abilities in religious education settings, particularly in Kesamben Village. The research methodology involves data collection through observation, interviews, and document analysis. The results of the research indicate a positive impact of the Iqro' method on the development of Quranic reading skills among participants in the Islamic Education Center in Kesamben Village.